(Un)Broken: Lateral violence among hospital nurses, user violence, burnout, and general health: A structural equation modeling analysis - Vidal-Alves, Maria Joao; Pina, David; Ruiz-Hernández, José Antonio; Puente-López, Esteban; Paniagua, David; Martínez-Jarreta, Begoña (Frontiers in Medicine, 2022)
Workplace violence is a social problem yet to be solved. Although it is present in virtually all work environments, its prevalence in healthcare settings stands out, being perceived as something inherent to the job. Most studies in this context have focused on user violence against professionals. However, it has been observed that violence among colleagues in these types of jobs is a risk factor for the health of workers and has rarely been studied as a whole. Among the main consequences of exposure to violence reported in the literature, burnout syndrome, depression, anxiety or somatic problems have been among the most studied. On the one hand, some authors claim that being exposed to workplace violence can increase the associated physical and psychological pathology and lead to a picture congruent with burnout. On the other hand, it has been hypothesized that violence is associated with burnout, which can trigger physical and psychological symptoms. Taking into account this background, the aim of this study is to explore workplace violence in health personnel, symptomatology and burnout syndrome through mediation models that allow us to know the interrelationships between the variables. Results. After controlling the mediation effects of burnout, physical and non-physical user violence towards healthcare personnel were significant predictors of the GHQ-28 scores. These same results were obtained when assessing the relationship between social, laboral and personal violence among co-workers and GHQ-28 scores. Regardless of the type of violence experienced, exposure to violence can lead to anxious, depressive or somatization symptoms, among others. Violence is also a predictor of burnout syndrome, which in turn accentuates the rest of the consequences studied. Despite the limitations of the proposed model, these results serve to highlight the complexity of the situation experienced by healthcare professionals. Moreover, it serves as a basis for proposing intervention/prevention programs to raise awareness and protect professionals from these risks. To this end, self-care tools should be proposed with which professionals take care of their own health through the management of violent situations and/or the improvement of occupational health.